2023
DOI: 10.3390/biomedicines11051485
|View full text |Cite
|
Sign up to set email alerts
|

Developing In Vitro Models to Define the Role of Direct Mitochondrial Toxicity in Frequently Reported Drug-Induced Rhabdomyolysis

Abstract: The United States Food and Drug Administration Adverse Event Reporting System (FAERS) logged 27,140 rhabdomyolysis cases from 2004 to 31 March 2020. We used FAERS to identify 14 drugs frequently reported in 6583 rhabdomyolysis cases and to investigate whether mitochondrial toxicity is a common pathway of drug-induced rhabdomyolysis by these drugs. Preliminary screening for mitochondrial toxicity was performed using the acute metabolic switch assay, which is adapted here for use in murine L6 cells. Fenofibrate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…found that pregabalin had a strong inhibitory effect on cellular oxidative phosphorylation, directly inhibiting electron transfer chain activity and inducing mitochondrial dysfunction, and preventing the synthesis of ATP. 21 …”
Section: Discussionmentioning
confidence: 99%
“…found that pregabalin had a strong inhibitory effect on cellular oxidative phosphorylation, directly inhibiting electron transfer chain activity and inducing mitochondrial dysfunction, and preventing the synthesis of ATP. 21 …”
Section: Discussionmentioning
confidence: 99%